Effects of latihan pasrah diri in quality of life in chronic kidney disease-dialysis patients with depression symptoms - Widyaningrum, Widyaningrum; Siswanto, Agus; Djarwoto, Bambang (Acta Interna The Journal of Internal Medicine, 2013)
ABSTRACTBackground: Patients with chronic kidney disease (CKD) suffering from various physical and emotional symptoms show depression and disturbance in quality of life. Patients with chronic kidney disease have a decreased quality of life, and mortality rate about 22% in every year. Depression in patients with CKD must be managed properly because a large effect on HRQOL (Health Related Quality of Life) and the potential side effects on the management of patients with CKD. Latihan pasrah diri (LPD) is a method combining relaxation and remembrance with a focus on breathing exercises and words contained in the dhikr (relaxation and repetitive prayer). The rise of the relaxation response is expected to improve the symptoms of stress or depressive symptoms, which is expected to improve HRQOL.Objective: This study aimed to determine the effect of LPD on quality of life in hemodialysis patients with depressive symptoms that was compared with controls.Methods: The research constituted the study of Randomized Control Trial. The research was measured the KDQOL-SF scores (Kidney Disease Quality of Life-SF) in subjects with LPD treatment during 21 days, compared with controls. The research was conducted at the Hemodialysis Unit of Dr. Sardjito Hospital, Yogyakarta, from May to June 2012. A total of 36 patients who met the inclusion criteria were randomized and divided into LPD group (n = 18) and control group (n = 18).Results: Found a statistically signifi cant decrease in BDI scores in both groups, 23.00 Â± 5.34 to 15.00 Â± 8.55 (p = 0.001) in the LPD group and 23.00 Â± 5.34 to18.33 Â± 6, 66 (p = 0.022) in the control group. KDQOL-SF scores after treatment when compared between the LPD and control groups experienced different changes were statistically signifi cant in domains effects of kidney disease 59.65 Â±23.52 compared to 39.41 Â± 20.03 (p = 0.022), sleep 69 Â± 13.17 compared to 46.53. (p = 0.000), overall health 73.89 Â± 16.85 compared to 57.22 Â± 19.04 (p = 0.009), pain 64.86 Â± 20.80 compared to 42.36 Â± 24.90 (p = 0.005), general health 53.88 Â±16.05 compared to 47.78 Â± 20.74 (p = 0.014), and the physical component scale 35.98 Â± 6, 83 compared to 29.12 Â± 6.46 (p = 0.004). Despite increased KDQOL-SF domain scores, but there were 2 domains that Î KDQOL-SF score changes were statistically signifi cantly different compared with the control group, which was the domain of sleep and overall health.Conclusion: Latihan pasrah diri twice a day during 21 days (3 weeks) can improved the quality of life of patients with symptoms depression in CKD patients undergoing hemodialysis in domains of sleep and overall health.Keywords: CKD, depression, latihan pasrah diri, KDQOL-SF.